The Co-Design of a Locally Led Health Professional Education Curriculum in Lao People’s Democratic Republic - Amy Gray; Sysavanh Phommachanh; Niranh Phoumindr; Mayfong Mayxay (International Medical Education)
(1) Background: There is a need to scale and transform health professional education (HPE) globally to not only improve the quantity but also the quality of health workers. This paper describes the approach undertaken by a Health University in Lao PDR. (2) Approach: The HPE curriculum was designed in an iterative process with key stakeholders from both the institution and government, with external expert advice. (3) Outcomes: The curriculum was successfully developed consisting of nine core modules and one elective module, reflecting both elements seen globally in HPE curricula as well as reflecting local needs. The content and teaching methods were validated and reviewed through piloting with local education leaders. (4) Conclusions: Despite the need to scale HPE globally, there are few examples of how this can be achieved in countries in which large gaps exist in HPE capacity. This paper provides one such example, through recognizing that sustained external partnerships will still be needed for successful future implementation.